2021
DOI: 10.1016/j.intfin.2021.101444
|View full text |Cite
|
Sign up to set email alerts
|

Economic stimulus through bank regulation: Government responses to the COVID-19 crisis

Abstract: In this paper, we estimate the effects of the COVID-19 pandemic on the banking system and the real economy and simulate potential policy responses. We combine machine learning algorithms, namely a Random Regression Forest and a Long Short Term Memory neural network, with an agent-based framework to calculate the expected results of the pandemic, according to different scenarios regarding financial stability. We then simulate government responses to this crisis and find that traditional demand and supply stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 111 publications
0
18
0
Order By: Relevance
“…In the cryptocurrency field, machine learning-based approaches, such as SVM and RF, are used for trading strategies (Sebastiao and Godinho 2021 ). RF and long short-term memory, which is a deep learning method, are combined to analyze the effect of COVID-19 on bank regulations (Polyzos et al 2021 ). We explained various machine learning regression methods used in this study in the following.…”
Section: Methodsmentioning
confidence: 99%
“…In the cryptocurrency field, machine learning-based approaches, such as SVM and RF, are used for trading strategies (Sebastiao and Godinho 2021 ). RF and long short-term memory, which is a deep learning method, are combined to analyze the effect of COVID-19 on bank regulations (Polyzos et al 2021 ). We explained various machine learning regression methods used in this study in the following.…”
Section: Methodsmentioning
confidence: 99%
“…This means that regulation leads to a lower level of resources available for economic activities. In this context, Polyzos et al (2021) have suggested relaxing bank regulations. However, Montgomery (2005) has found that the regulatory capital ratio does not have any effect on bank portfolios.…”
Section: Source(s): Gmpi Imf Databasementioning
confidence: 99%
“…This means that regulation leads to a lower level of resources available for economic activities. In this context, Polyzos et al. (2021) have suggested relaxing bank regulations.…”
Section: Background Literaturementioning
confidence: 99%
See 2 more Smart Citations